Pengembangan Objek Wisata Danau Uter Dan Puncak Petik Bintang Dalam Peningkatan Pendapatan Asli Daerah Di Kabupaten Maybrat Provinsi Papua Barat - Erdy Andre Rumbang (UIR Press, 2022)
Tourism development is a strategy used to promote, improve and improve the tourism conditions of an object and a tourist attraction so that tourists can be interested in visiting in the end, it is expected to be able to provide benefits to the community around the tourist attraction and to the government. The purpose of this study is to find out and analyze how the development of tourism objects, what are the driving and inhibiting factors and strategies that need to be carried out in the development of Danau Uter and Gunung Petik Bintang tourism objects in increasing Regional Original Income in Maybrat Regency. The research method uses a qualitative approach, data collection techniques are observation, interviews, and documentation. The results of this research are: 1). The development of tourist objects is less supportive and less effective in implementing it, this can be seen from the 4 (four) indicators of tourism object development, only 1 (one) supports it, namely, Attractions, while the other 3 (three) are less supportive, namely service , promotions, information and transportation. 2) The driving and inhibiting factors for the development of Danau Uter and Puncak Petik Bintang tourism objects in increasing Regional Original Income in Maybrat Regency are 1) Pushing factors: (a) The existence of laws and regulations, regional regulations, (b) the existence of the carrying capacity of the natural potential of Lake Uter and Mount Petik Bintang tourism objects, (c) the existence of the carrying capacity of cultural diversity, customs, (d) the strategic position of the Maybrat Regency (e) ) The friendliness of the population, (f) The existence of technological sophistication, (g) Availability of tourist service facilities, 2) Inhibiting Factors: (a) Limited budget, (b) Lack of support for the fulfillment of other supporting facilities and infrastructure at tourism objects, (c) Access to transportation and infrastructure is less supportive and limited, (d) Access to promotion and information is lacking support, (e) the issue of the low level of security and (f) the low level of public understanding about Tourism Awareness and Sapta Pesona. 3) Strategies, namely: 1) Increasing Tourism Security and Preservation of Tourism Objects, 2) Forming Tourism Awareness Groups and Sapta Pesona, 3) Increasing Promotion and Marketing of Tourism Objects, 4) Fulfilling Tourism Amenities and 5) Increasing Transportation and Improved Infrastructure Quality.